Glass fiber reinforced plastic thread elastic sealant as well as preparation method and application thereof
Through the design of two-component sealant, the use of liquid polysulfide glue and thermoplastic elastomer and other materials, the problem of low bond strength and insufficient toughness in high temperature and temperature difference changes is solved, and the efficient sealing effect is achieved , suitable for the long-term use of fiberglass integrated transportation pipelines.
Patent Information
- Application Number
- CN202310809447.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-03
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-07-03
AI Technical Summary
The existing fiberglass thread sealant has low bond strength and insufficient toughness in high temperature and temperature difference environments, resulting in leakage and tripping problems at the threaded connections of fiberglass integrated transportation pipelines.
Two-component sealant using components A and B, components A include liquid polysulfide glue, 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde, epoxy resin E-51 , thermoplastic elastomer TPV, rubber and plastic alloy, vapor phase silica and reinforced carbon black, components B include manganese dioxide, epoxy curing agent, sulfur powder, microcrystalline wax, calcium carbonate and 2,4,6-3 (Dimethylamine methyl)phenol is prepared by mixing and processing in specific proportions to prepare a fiberglass thread sealant with high elasticity and strong adhesiveness.
The sealant maintains good bonding strength and toughness in high temperature and temperature difference changing environments, can effectively seal the leakage gap of fiberglass threads, has a strong sealing effect, and can withstand media erosion and vibration environment for a long time.
Smart Images

Figure BDA0004319116880000141 
Figure BDA0004319116880000151 
Figure HDA0004319116890000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass fiber reinforced plastic pipe thread connection, and specifically relates to a glass fiber reinforced plastic thread elastic sealant and a preparation method and application thereof. Background Art
[0002] Glass fiber reinforced plastic is a composite material formed by reinforcing a specific resin with glass fiber. It has the advantages of light material, strong corrosion resistance, smooth inner surface, low friction coefficient and small heat transfer coefficient. With the continuous development of the oil and gas industry, a large number of metal gathering and transportation pipelines have been laid in the oil field operation area. Although multiple anti-corrosion measures such as internal and external anti-corrosion coatings and corrosion inhibitors have been taken, leakage or scaling due to corrosion will continue to occur over time, and leakage, environmental pollution and other problems will occur, seriously affecting normal production operations. In view of the many advantages of FRP gathering and transportation pipelines, it has been used in the field of gathering and transportation pipelines in oil fields. FRP gathering and transportation pipelines are connected to long-distance transmission pipelines through threads. Before the threads are twisted, they must be evenly coated with curable FRP thread sealants to ensure the overall sealing of the pipeline. However, during the actual operation of FRP gathering and transportation pipelines, due to the influence of pressure fluctuations in the gathering and transportation system, vibrations caused by fluid flow, and ground temperature, thread disengagement or leakage may occur during on-site use. According to relevant data, the most accidents in FRP gathering and transportation pipelines are in the threaded connection part.
[0003] After the laying of FRP gathering and transportation pipelines is completed, they need to be used for a long time, so the sealants at the joints between pipes must also have long-term performance. However, the existing FRP thread sealant products have the problems of too large a change in curing time with temperature, low bonding strength and insufficient toughness. Summary of the invention
[0004] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a fiberglass reinforced plastic thread elastic sealant and a preparation method and application thereof. The sealant has the characteristics of high elasticity, high bonding strength, strong medium resistance, etc., can maintain high bonding strength and suitable curing time and excellent toughness in high and low temperature environments, can effectively seal the leakage gap of fiberglass reinforced plastic threads, and has a strong sealing effect.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The invention provides a glass fiber reinforced plastic thread elastic sealant, which comprises a component A and a component B, wherein the mass ratio of the component A to the component B is 20:(4-5); in terms of weight percentage, the constituent raw materials of the component A comprise: 15%-25% of liquid polysulfide glue, 10%-16% of 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde, 10%-15% of epoxy resin E-51, 7%-13% of thermoplastic elastomer TPV, 8%-14% of rubber-plastic alloy, 7%-13% of dibutyl phthalate, 1%-5% of fumed silica, 0.5%-2% of a defoaming agent, and 15%-25% of reinforcing carbon black, and the sum of the weight percentages of all constituent raw materials of the component A is 100%;
[0007] The raw materials of component B include: 7% to 13% manganese dioxide, 8% to 12% epoxy curing agent, 1% to 2% sulfur powder, 15% to 18% microcrystalline wax, 25% to 35% calcium carbonate powder, 25% to 32% dibutyl phthalate, and 1% to 5% 2,4,6-tris(dimethylaminomethyl)phenol. The total weight percentage of all the raw materials of component B is 100%.
[0008] The present invention also provides a method for preparing the fiberglass reinforced plastic thread elastic sealant, comprising the following steps:
[0009] Prepare 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde, mix liquid polysulfide rubber, 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde, epoxy resin E-51, thermoplastic elastomer TPV, rubber-plastic alloy, dibutyl phthalate, fumed silica, defoaming agent and reinforcing carbon black according to a certain proportion to obtain component A;
[0010] Manganese dioxide, epoxy curing agent, sulfur powder, microcrystalline wax, calcium carbonate powder, dibutyl phthalate and 2,4,6-tris(dimethylaminomethyl)phenol are mixed according to a certain proportion to prepare component B;
[0011] Component A and component B are mixed in a mass ratio of 20:(4-5) to prepare a fiberglass reinforced plastic thread elastic sealant.
[0012] In a specific implementation process, the preparation of 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde comprises the following steps:
[0013] S1: 5-bromo-3-fluoro-2-hydroxybenzaldehyde and dibromoethane are mixed and dissolved in N,N-dimethylformamide, and then anhydrous potassium carbonate is added, and the temperature is raised to a first set temperature and reacted for a first set time. After the reaction is completed, the temperature is lowered to room temperature, and then the organic phases are extracted, combined and washed, and the organic phases are post-treated to obtain 5-bromo-3-fluoro-2-(2-bromoethoxy)-benzaldehyde;
[0014] S2: Dissolve 5-bromo-3-fluoro-2-(2-bromoethoxy)-benzaldehyde in anhydrous tetrahydrofuran, cool to a second set temperature under a protective gas, add potassium tert-butoxide, stir and react at a third set temperature for a second set time, and after the reaction is completed, purify the reaction solution to obtain 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde.
[0015] In a specific implementation process, in S1, the mass ratio of 5-bromo-3-fluoro-2-hydroxybenzaldehyde to dibromoethane is (18-23): (20-26).
[0016] In the specific implementation process, in S1, the mass ratio of dibromoethane to anhydrous potassium carbonate is (20-26): (13-20).
[0017] In the specific implementation process, in S1, the first set temperature is 75-85° C., and the first set time is 15-17 hours.
[0018] In the specific implementation process, in S2, the mass ratio of 5-bromo-3-fluoro-2-(2-bromoethoxy)-benzaldehyde to potassium tert-butoxide is (17-23):(5-10).
[0019] In the specific implementation process, in S2, the second set temperature is -18 to -22°C, the third set temperature is -17 to -22°C, and the second set time is 1 to 2 hours.
[0020] The present invention also provides an application of the FRP thread elastic sealant in a FRP pipe.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention provides a fiberglass thread elastic sealant, comprising component A and component B, wherein the introduction of 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde monomer in component A is mainly to introduce fluorine atoms into the entire system, giving the system rubber excellent heat resistance, oxidation resistance, oil resistance, corrosion resistance and atmospheric aging resistance, so that the sealant of the present invention can not only adapt to conventional working conditions but also adapt to harsh environments such as high temperatures in deserts and Gobi deserts, and large temperature differences between the four seasons. Liquid polysulfide rubber is used as the preparation raw material. After the polysulfide rubber is polymerized with manganese dioxide, it has excellent properties such as oil resistance, solvent resistance, oxygen and ozone resistance, water resistance, high and low temperature resistance, etc., has a long storage time, good flexibility, can maintain the sealing of the fiberglass thread for a long time, and can also adapt to the vibration of the pipeline caused by the change of the medium pressure inside the fiberglass pipeline and the ambient temperature. Epoxy resin can make up for the lack of bonding strength of polysulfide rubber. Thermoplastic elastomer TPV has excellent dynamic fatigue resistance, high tear resistance, compression deformation resistance, excellent weather resistance, good wear resistance and excellent flame retardancy and UV resistance, and has excellent corrosion resistance to water-based acid and alkali liquids and polar oils. The introduction of this filler is mainly to improve the dynamic fatigue resistance and tear resistance of the entire system, and also improve the toughness. Adding it to the glass agent will greatly improve the toughness, weather resistance and other comprehensive properties of the product. Rubber-plastic alloy is an excellent oil-resistant material with high strength, oil resistance, solvent resistance, weather resistance and heat aging resistance, and is suitable for long-term service operations. Dibutyl phthalate is used as a plasticizer to increase the softness of the system. Fumed silica is used as a thickener to adjust the thinness and consistency of the system. Defoaming agent is used to prevent foam formation or reduce the original foam. Reinforcing carbon black is used as a filler to improve the strength of the system. The manganese dioxide powder in component B of the system is the initiator of polysulfide rubber; sulfur powder is the accelerator of the polymerization of polysulfide rubber initiated by manganese dioxide; calcium carbonate is used as a filler; 910 toughened epoxy curing agent is an epoxy curing agent, which also has the function of improving the toughness of the system; microcrystalline wax has good flexibility and large elongation, and is used to improve the gloss of the system.
[0023] The fiberglass thread sealant of the present invention can withstand the erosion and impact of the conveying medium for a long time, the changes in the vibration environment temperature caused by the pressure change of the conveying medium, and other factors. The fiberglass thread sealant has good weather resistance and corrosion resistance, can adapt to the surrounding environment temperature and has good toughness, and can withstand long-term multi-frequency vibration and pressure shock. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The figure is a process diagram for preparing 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde according to the present invention. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0026] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0027] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0028] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0029] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0030] The invention provides a glass fiber reinforced plastic thread elastic sealant, a preparation method and an application thereof.
[0031] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0032] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0033] The present invention provides a fiberglass thread elastic sealant, which comprises component A and component B, and the mass ratio of component A to component B is 20:(4-5) by weight percentage. Component A comprises: 15%-25% of liquid polysulfide glue, 10%-16% of 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde, 10%-15% of epoxy resin E-51, 7%-13% of thermoplastic elastomer TPV, 8%-14% of rubber-plastic alloy, 7%-13% of dibutyl phthalate, 1%-5% of fumed silica, 0.5%-2% of defoaming agent, and 15%-25% of reinforcing carbon black. The weight percentage of all components is 1:1. The sum of the percentages is 100%; the liquid polysulfide rubber is JLY-124 type produced by Jinxi Chemical Research Institute Co., Ltd. This material is a raw material for preparing polysulfide rubber. After the polymerization of polysulfide rubber and manganese dioxide, it has excellent properties such as oil resistance, solvent resistance, oxygen and ozone resistance, water resistance, high and low temperature resistance, long storage time, good flexibility, and can maintain the sealing of the FRP thread for a long time. At the same time, it can also adapt to the vibration of the pipeline caused by changes in the internal medium pressure of the FRP pipeline and the ambient temperature.
[0034] The introduction of 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde monomer is mainly to introduce fluorine atoms into the entire system, giving the system rubber excellent heat resistance, oxidation resistance, oil resistance, corrosion resistance and atmospheric aging resistance, so that the invention can not only adapt to conventional working conditions but also adapt to harsh environments such as high temperatures in deserts and Gobi deserts, and large temperature differences between the four seasons.
[0035] E-51 epoxy resin is designed to make up for the insufficient bonding strength of polysulfide adhesive. This product uses Phoenix brand epoxy resin, and the above raw materials are easy to purchase on the market.
[0036] Thermoplastic elastomer TPV has excellent dynamic fatigue resistance, high tear resistance, compression deformation resistance, excellent weather resistance, good wear resistance and excellent flame retardancy and UV resistance, and has excellent corrosion resistance to water-based acid and alkali liquids and polar oils. The introduction of this filler is mainly to improve the dynamic fatigue resistance and tear resistance of the entire system, and also improve the toughness. Adding it to this system will greatly improve the toughness, weather resistance and other comprehensive properties of the product of the invention. This project selects the Kraton model sold by Shanghai Waidian International Trading Co., Ltd.: SEBS thermoplastic elastomer TPV.
[0037] The rubber-plastic alloy is an excellent oil-resistant material with high strength, oil resistance, solvent resistance, weather resistance and heat aging resistance, and is suitable for long-term service operation. The material used in the present invention is NV3460-3H produced by Hengshui Ruien Rubber & Plastic Technology Co., Ltd.
[0038] Dibutyl phthalate is a common plasticizer that increases the softness of the system. The above raw materials are easily available on the market.
[0039] Fumed silica is a thickener used to adjust the consistency of the system. The present invention selects A380 produced by Degussa.
[0040] The surface tension of the defoamer system prevents the formation of foam or reduces the original foam. The project selected is Yantai Hengxin Chemical Technology Co., Ltd. X-278 defoamer.
[0041] The reinforcing carbon black is mainly used as a filler and to improve the strength of the system. The present invention uses American Cabot carbon black N550.
[0042] Component B comprises: 7% to 13% manganese dioxide, 8% to 12% epoxy curing agent, preferably 910 toughened epoxy curing agent, 1% to 2% sulfur powder, 15% to 18% microcrystalline wax, 25% to 35% calcium carbonate powder, 25% to 32% dibutyl phthalate, and 1% to 5% 2,4,6-tris(dimethylaminomethyl)phenol, and the sum of the weight percentages of all components is 100%.
[0043] Manganese dioxide powder is the initiator of polysulfide glue; sulfur powder is the accelerator of polysulfide glue polymerization initiated by manganese dioxide; calcium carbonate is a filler, and DMP-30 is the accelerator of epoxy resin curing in the system. The above components are easy to buy on the market. The particle size of the above powder components is selected to be in the range of 30 to 60 microns. 910 toughened epoxy curing agent is an epoxy curing agent, which also has the function of improving the toughness of the system. This product can be purchased from Changsha Chemical Research Institute. Microcrystalline wax has good flexibility and large elongation, which improves the gloss of the system. This system selects the 70# microcrystalline wax product produced by Sinopec.
[0044] The present invention also provides a method for preparing a fiberglass reinforced plastic thread elastic sealant, comprising the following steps:
[0045] Preparation of component A:
[0046] Step 1: Preparation of 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde:
[0047] like Figure 1As shown, the compound 5-bromo-3-fluoro-2-hydroxybenzaldehyde and dibromoethane in a mass ratio of (18-23): (20-26) are dissolved in DMF, anhydrous potassium carbonate (13-20g) is added, and the mass ratio of dibromoethane to anhydrous potassium carbonate is (20-26): (13-20), and the temperature is raised to 75-85°C for reaction for 15-17h. Cool to room temperature, pour the reaction solution into water (480-510mL), and then extract with ethyl acetate (190-210mL), combine the organic phases, and wash with saturated brine (190-210mL). The organic phase is dried over anhydrous sodium sulfate, filtered, and the filtrate is concentrated under reduced pressure and purified by silica gel column chromatography to obtain a yellow oil.
[0048] The obtained product No. 1 5-bromo-3-fluoro-2-(2-bromoethoxy)-benzaldehyde (17-23 g) was dissolved in anhydrous THF (140-160 mL), cooled to -18--22° C. under nitrogen protection, and potassium tert-butoxide (5-10 g) was added, the mass ratio of 5-bromo-3-fluoro-2-(2-bromoethoxy)-benzaldehyde to potassium tert-butoxide was (17-23): (5-10), and stirred at -17--22° C. for 1-2 hours. After the reaction was completed, the reaction solution was directly and quickly purified by a silica gel column to obtain a yellow oily substance, namely the product No. 2 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde.
[0049] Step 2: Mix liquid polysulfide rubber, 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde, epoxy resin E-51, thermoplastic elastomer TPV, rubber-plastic alloy, dibutyl phthalate, fumed silica, defoamer and reinforcing carbon black according to a certain proportion for 1 to 1.5 hours to obtain component A;
[0050] Step 3: Mix manganese dioxide, 910 toughened epoxy curing agent, sulfur powder, microcrystalline wax, calcium carbonate, calcium carbonate powder, dibutyl phthalate and 2,4,6-tris(dimethylaminomethyl)phenol in proportion and stir for 2 to 2.5 hours to obtain component B;
[0051] Step 4: Mix component A and component B in a mass ratio of 100:(20-25) to prepare a fiberglass thread elastic sealant.
[0052] Use the provided brush to evenly apply the FRP thread elastic sealant to the FRP thread surface as a sealant for the FRP gathering pipeline.
[0053] Embodiment 1:
[0054] The weight ratio of the components of component A is: liquid polysulfide rubber 20%, 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde 13%, epoxy resin E-51 12%, thermoplastic elastomer TPV 10%, rubber-plastic alloy 11%, dibutyl phthalate 10%, fumed silica 3%, defoamer 1%, and reinforcing carbon black 20%.
[0055] Wherein 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde in component A is prepared according to the following method:
[0056] Step 1: Dissolve the compound 5-bromo-3-fluoro-2-hydroxybenzaldehyde (21.9 g, 0.10 mol) and dibromoethane (22.5 g, 0.12 mol) in DMF (250 mL), add anhydrous potassium carbonate (16.6 g, 0.12 mol), and heat to 80 ° C for 16 hours. Cool to room temperature, pour the reaction solution into water (500 mL), and then extract three times with ethyl acetate (200 mL), combine the organic phases, and wash with saturated brine (200 mL). The organic phase is dried over anhydrous sodium sulfate, filtered, and the filtrate is concentrated under reduced pressure and purified by silica gel column chromatography to obtain 22.2 g of yellow oil, with a yield of about 68%.
[0057] Step 2: Dissolve the product 5-bromo-3-fluoro-2-(2-bromoethoxy)-benzaldehyde (20.0 g, 61.3 mmol) obtained in step 1 in anhydrous THF (150 mL), cool to -20°C under nitrogen protection, add potassium tert-butoxide (7.2 g, 64.4 mmol), and stir at -17°C for 1 hour. After the reaction, the reaction solution is directly and quickly purified by silica gel column to obtain 8.3 g of yellow oily 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde, with a yield of about 55%.
[0058] The product No. 2 is 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde.
[0059] The weight ratio of the components of component B is: 10% manganese dioxide, 10.5% 910 toughened epoxy curing agent, 1.5% sulfur powder, 17% microcrystalline wax, 30% calcium carbonate powder, 28% dibutyl phthalate, and 3% DMP-30.
[0060] The preparation method is: first prepare 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde according to the above process, then mix and stir according to the above proportion of component A for 1 hour to prepare component A; component B is mixed and stirred for 2.5 hours according to the above proportion. After component A and component B are prepared, they can be used after being stirred evenly according to component A: component B = 100:22 before use, and evenly applied to the surface of the fiberglass thread with a brush.
[0061] Embodiment 2:
[0062] The weight ratio of the components of component A is: liquid polysulfide rubber 23%, 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde 11%, epoxy resin E-51 13%, thermoplastic elastomer TPV 12%, rubber-plastic alloy 9%, dibutyl phthalate 11%, fumed silica 4%, defoamer 1%, and reinforcing carbon black 16%.
[0063] Wherein 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde in component A is prepared according to the following method:
[0064] Step 1: Dissolve the compound 5-bromo-3-fluoro-2-hydroxybenzaldehyde (21.9 g, 0.10 mol) and dibromoethane (22.5 g, 0.12 mol) in DMF (250 mL), add anhydrous potassium carbonate (16.6 g, 0.12 mol), and heat to 80 ° C for 16 hours. Cool to room temperature, pour the reaction solution into water (500 mL), and then extract with ethyl acetate (200 mL x 3), combine the organic phases, and wash with saturated brine (200 mL). The organic phase is dried over anhydrous sodium sulfate, filtered, and the filtrate is concentrated under reduced pressure and purified by silica gel column chromatography to obtain 22.2 g of yellow oil with a yield of about 68%.
[0065] Step 2: Dissolve the product 5-bromo-3-fluoro-2-(2-bromoethoxy)-benzaldehyde (20.0 g, 61.3 mmol) obtained in step 1 in anhydrous THF (150 mL), cool to -20°C under nitrogen protection, add potassium tert-butoxide (7.2 g, 64.4 mmol), and stir at -19°C for 1 hour. After the reaction, the reaction solution is directly and quickly purified by silica gel column to obtain 8.3 g of yellow oily 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde, with a yield of about 55%.
[0066] The product No. 2 is 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde.
[0067] The weight ratio of the components of component B is: 12% manganese dioxide, 11.5% 910 toughened epoxy curing agent, 1.5% sulfur powder, 15% microcrystalline wax, 30% calcium carbonate powder, 27% dibutyl phthalate, and 3% DMP-30.
[0068] The preparation method is: first prepare 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde according to the above process, then mix and stir according to the above proportion of component A for 1 hour to prepare component A; component B is mixed and stirred for 2 hours according to the above proportion. After component A and component B are prepared, they can be used after being stirred evenly according to component A: component B = 100:22 before use, and evenly applied to the surface of the fiberglass thread with a brush.
[0069] Embodiment 3:
[0070] The weight ratio of the components of component A is: liquid polysulfide rubber 20%, 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde 14%, epoxy resin E-51 11%, thermoplastic elastomer TPV 10%, rubber-plastic alloy 11%, dibutyl phthalate 12%, fumed silica 3%, defoamer 1%, and reinforcing carbon black 18%.
[0071] Wherein 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde in component A is prepared according to the following method:
[0072] Step 1: Dissolve the compound 5-bromo-3-fluoro-2-hydroxybenzaldehyde (21.9 g, 0.10 mol) and dibromoethane (22.5 g, 0.12 mol) in DMF (250 mL), add anhydrous potassium carbonate (16.6 g, 0.12 mol), and heat to 80 ° C for 16 hours. Cool to room temperature, pour the reaction solution into water (500 mL), then extract with ethyl acetate (200 mL x 3), combine the organic phases, and wash with saturated brine (200 mL). The organic phase is dried over anhydrous sodium sulfate, filtered, and the filtrate is concentrated under reduced pressure and purified by silica gel column chromatography to obtain 22.2 g of a yellow oil with a yield of about 68%.
[0073] Step 2: Dissolve the product 5-bromo-3-fluoro-2-(2-bromoethoxy)-benzaldehyde (20.0 g, 61.3 mmol) obtained in step 1 in anhydrous THF (150 mL), cool to -20°C under nitrogen protection, add potassium tert-butoxide (7.2 g, 64.4 mmol), and stir at -20°C for 1 hour. After the reaction, the reaction solution is directly and quickly purified by silica gel column to obtain 8.3 g of yellow oily 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde, with a yield of about 55%.
[0074] The product No. 2 is 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde.
[0075] The weight ratio of the components of component B is: 11% manganese dioxide, 10.5% 910 toughened epoxy curing agent, 1.5% sulfur powder, 16% microcrystalline wax, 29% calcium carbonate powder, 29% dibutyl phthalate, and 3% DMP-30.
[0076] The preparation method is: first prepare 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde according to the above process, then mix and stir according to the above proportion of component A for 1.2 hours to prepare component A; component B is mixed and stirred for 2.2 hours according to the above proportion. After component A and component B are prepared, they can be used after being stirred evenly according to component A: component B = 100:23 before use, and evenly applied to the surface of the fiberglass thread with a brush.
[0077] Embodiment 4:
[0078] The weight ratio of the components of component A is: liquid polysulfide rubber 15%, 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde 16%, epoxy resin E-51 15%, thermoplastic elastomer TPV 13%, rubber-plastic alloy 14%, dibutyl phthalate 7%, fumed silica 1%, defoamer 0.5%, and reinforcing carbon black 18.5%.
[0079] Wherein 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde in component A is prepared according to the following method:
[0080] Step 1: Dissolve the compound 5-bromo-3-fluoro-2-hydroxybenzaldehyde (18.0 g) and dibromoethane (20.0 g) in DMF (250 mL), add anhydrous potassium carbonate (13.0 g), and heat to 75 ° C for 15 hours. Cool to room temperature, pour the reaction solution into water (500 mL), and then extract with ethyl acetate (200 mL x 3), combine the organic phases, and wash with saturated brine (200 mL). The organic phase is dried over anhydrous sodium sulfate, filtered, and the filtrate is concentrated under reduced pressure and purified by silica gel column chromatography to obtain a yellow oil.
[0081] Step 2: Dissolve the product 5-bromo-3-fluoro-2-(2-bromoethoxy)-benzaldehyde (17.0 g) obtained in step 1 in anhydrous THF (150 mL), cool to -20°C under nitrogen protection, add potassium tert-butoxide (5.0 g), and stir at -18°C for 1 hour. After the reaction, the reaction solution is directly and quickly purified by silica gel column to obtain yellow oil 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde.
[0082] The product No. 2 is 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde.
[0083] The weight ratio of the components of component B is: 13% manganese dioxide, 12% 910 toughened epoxy curing agent, 1% sulfur powder, 18% microcrystalline wax, 30% calcium carbonate powder, 25% dibutyl phthalate, and 1% DMP-30.
[0084] The preparation method is: first prepare 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde according to the above process, then mix and stir according to the above proportion of component A for 1 hour to prepare component A; component B is mixed and stirred for 2 hours according to the above proportion. After component A and component B are prepared, they can be used after being stirred evenly according to component A: component B = 100:20 before use, and evenly applied to the surface of the fiberglass thread with a brush.
[0085] Embodiment 5:
[0086] The weight ratio of the components of component A is: liquid polysulfide rubber 25%, 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde 10%, epoxy resin E-51 10%, thermoplastic elastomer TPV 7%, rubber-plastic alloy 8%, dibutyl phthalate 13%, fumed silica 5%, defoamer 2%, and reinforcing carbon black 20%.
[0087] Wherein 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde in component A is prepared according to the following method:
[0088] Step 1: Dissolve the compound 5-bromo-3-fluoro-2-hydroxybenzaldehyde (23.0 g) and dibromoethane (26.0 g) in DMF (250 mL), add anhydrous potassium carbonate (20.0 g), and heat to 85°C for 17 hours. Cool to room temperature, pour the reaction solution into water (500 mL), and then extract with ethyl acetate (200 mL x 3), combine the organic phases, and wash with saturated brine (200 mL). The organic phase is dried over anhydrous sodium sulfate, filtered, and the filtrate is concentrated under reduced pressure and purified by silica gel column chromatography to obtain a yellow oil.
[0089] Step 2: Dissolve the product 5-bromo-3-fluoro-2-(2-bromoethoxy)-benzaldehyde (23.0 g) obtained in step 1 in anhydrous THF (150 mL), cool to -20°C under nitrogen protection, add potassium tert-butoxide (10.0 g), and stir at -17 to -22°C for 1 hour. After the reaction, the reaction solution is directly and quickly purified by silica gel column to obtain yellow oil 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde.
[0090] The product No. 2 is 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde.
[0091] The weight ratio of the components of component B is: manganese dioxide 7%, 910 toughened epoxy curing agent 8%, sulfur powder 2%, microcrystalline wax 15%, calcium carbonate powder 35%, dibutyl phthalate 32%, and DMP-30 1%.
[0092] The preparation method is: first prepare 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde according to the above process, then mix and stir according to the above proportion of component A for 1.5 hours to prepare component A; component B is mixed and stirred for 2.5 hours according to the above proportion. After component A and component B are prepared, they can be used after being stirred evenly according to component A: component B = 100:25 before use, and evenly applied to the surface of the fiberglass thread with a brush.
[0093] Embodiment 6:
[0094] The weight ratio of the components of component A is: 15% liquid polysulfide rubber, 13% 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde, 15% epoxy resin E-51, 13% thermoplastic elastomer TPV, 14% rubber-plastic alloy, 13% dibutyl phthalate, 1% fumed silica, 1% defoaming agent, and 15% reinforcing carbon black.
[0095] Wherein 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde in component A is prepared according to the following method:
[0096] Step 1: Dissolve the compound 5-bromo-3-fluoro-2-hydroxybenzaldehyde (20.0 g) and dibromoethane (23.0 g) in DMF (250 mL), add anhydrous potassium carbonate (15.0 g), and heat to 80 ° C for 16 hours. Cool to room temperature, pour the reaction solution into water (500 mL), and then extract with ethyl acetate (200 mL x 3), combine the organic phases, and wash with saturated brine (200 mL). The organic phase is dried over anhydrous sodium sulfate, filtered, and the filtrate is concentrated under reduced pressure and purified by silica gel column chromatography to obtain a yellow oil.
[0097] Step 2: Dissolve the product 5-bromo-3-fluoro-2-(2-bromoethoxy)-benzaldehyde (22.0 g) obtained in step 1 in anhydrous THF (150 mL), cool to -20°C under nitrogen protection, add potassium tert-butoxide (8.0 g), and stir at -17°C for 1 hour. After the reaction, the reaction solution is directly and quickly purified by silica gel column to obtain yellow oil 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde.
[0098] The product No. 2 is 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde.
[0099] The weight ratio of the components of component B is: 13% manganese dioxide, 8% 910 toughened epoxy curing agent, 2% sulfur powder, 18% microcrystalline wax, 25% calcium carbonate powder, 29% dibutyl phthalate, and 5% DMP-30.
[0100] The preparation method is: first prepare 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde according to the above process, then mix and stir according to the above proportion of component A for 1 hour to prepare component A; component B is mixed and stirred for 2 hours according to the above proportion. After component A and component B are prepared, they can be used after being stirred evenly according to component A: component B = 100:24 before use, and evenly applied to the surface of the fiberglass thread with a brush.
[0101] Embodiment 7:
[0102] The weight ratio of the components of component A is: 20% liquid polysulfide rubber, 10% 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde, 12% epoxy resin E-51, 12% thermoplastic elastomer TPV, 9% rubber-plastic alloy, 7% dibutyl phthalate, 4% fumed silica, 1% defoaming agent, and 25% reinforcing carbon black.
[0103] Wherein 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde in component A is prepared according to the following method:
[0104] Step 1: Dissolve the compound 5-bromo-3-fluoro-2-hydroxybenzaldehyde (21.9 g, 0.10 mol) and dibromoethane (22.5 g, 0.12 mol) in DMF (250 mL), add anhydrous potassium carbonate (16.6 g, 0.12 mol), and heat to 80 ° C for 16 hours. Cool to room temperature, pour the reaction solution into water (500 mL), and then extract with ethyl acetate (200 mL x 3), combine the organic phases, and wash with saturated brine (200 mL). The organic phase is dried over anhydrous sodium sulfate, filtered, and the filtrate is concentrated under reduced pressure and purified by silica gel column chromatography to obtain a yellow oil.
[0105] Step 2: Dissolve the product 5-bromo-3-fluoro-2-(2-bromoethoxy)-benzaldehyde (20.0 g, 61.3 mmol) obtained in step 1 in anhydrous THF (150 mL), cool to -20°C under nitrogen protection, add potassium tert-butoxide (7.2 g, 64.4 mmol), and stir at -22°C for 1 hour. After the reaction, the reaction solution is directly and quickly purified by silica gel column to obtain yellow oil 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde.
[0106] The product No. 2 is 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde.
[0107] The weight ratio of the components of component B is: 12% manganese dioxide, 12% 910 toughened epoxy curing agent, 2% sulfur powder, 15% microcrystalline wax, 25% calcium carbonate powder, 32% dibutyl phthalate, and 2% DMP-30.
[0108] The preparation method is: first prepare 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde according to the above process, then mix and stir according to the above proportion of component A for 1.5 hours to prepare component A; and mix and stir component B according to the above proportion for 2.5 hours. After component A and component B are prepared, they can be used after being stirred evenly according to component A: component B = 100:21 before use, and evenly applied to the surface of the fiberglass thread with a brush.
[0109] The two-component fiberglass thread sealant prepared according to the above formula and process can be prepared into a sealant product with the advantages of high toughness, vibration resistance, corrosion resistance and high medium sealing after uniform mixing.
[0110] Performance testing:
[0111]
[0112]
[0113] The invention relates to a sealant used at a fiberglass reinforced plastic pipe thread connection. The sealant has the characteristics of high elasticity, high bonding strength, strong medium resistance, etc., can effectively block the leakage gap of the fiberglass reinforced plastic thread, and has a strong sealing effect.
[0114] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A fiberglass thread elastic sealant, characterized in that: The fiberglass thread elastic sealant comprises a component A and a component B, wherein the mass ratio of the component A to the component B is 20:(4-5); The raw materials of component A include, by weight percentage, 15% to 25% of liquid polysulfide, 10% to 16% of 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde, 10% to 15% of epoxy resin E-51, 7% to 13% of thermoplastic elastomer TPV, 8% to 14% of rubber-plastic alloy, 7% to 13% of dibutyl phthalate, 1% to 5% of fumed silica, 0.5% to 2% of defoaming agent, and 15% to 25% of reinforcing carbon black, and the sum of the weight percentages of all the raw materials of component A is 100%; The raw materials of component B include: 7% to 13% manganese dioxide, 8% to 12% epoxy curing agent, 1% to 2% sulfur powder, 15% to 18% microcrystalline wax, 25% to 35% calcium carbonate powder, 25% to 32% dibutyl phthalate, and 1% to 5% 2,4,6-tris(dimethylaminomethyl)phenol. The total weight percentage of all the raw materials of component B is 100%.
2. A method for preparing the fiberglass reinforced plastic thread elastic sealant according to claim 1, characterized in that: The following steps are involved: Prepare 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde, mix liquid polysulfide rubber, 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde, epoxy resin E-51, thermoplastic elastomer TPV, rubber-plastic alloy, dibutyl phthalate, fumed silica, defoaming agent and reinforcing carbon black according to a certain proportion to obtain component A; Manganese dioxide, epoxy curing agent, sulfur powder, microcrystalline wax, calcium carbonate powder, dibutyl phthalate and 2,4,6-tris(dimethylaminomethyl)phenol are mixed according to a certain proportion to prepare component B; Component A and component B are mixed in a mass ratio of 20:(4-5) to prepare a fiberglass reinforced plastic thread elastic sealant.
3. The method for preparing the fiberglass reinforced plastic thread elastic sealant according to claim 2, characterized in that: The preparation of 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde comprises the following steps: S1: 5-bromo-3-fluoro-2-hydroxybenzaldehyde and dibromoethane are mixed and dissolved in N,N-dimethylformamide, and then anhydrous potassium carbonate is added, and the temperature is raised to a first set temperature and reacted for a first set time. After the reaction is completed, the temperature is lowered to room temperature, and then the organic phases are extracted, combined and washed, and the organic phases are post-treated to obtain 5-bromo-3-fluoro-2-(2-bromoethoxy)-benzaldehyde; S2: Dissolve 5-bromo-3-fluoro-2-(2-bromoethoxy)-benzaldehyde in anhydrous tetrahydrofuran, cool to a second set temperature under a protective gas, add potassium tert-butoxide, stir and react at a third set temperature for a second set time, and after the reaction is completed, purify the reaction solution to obtain 5-bromo-3-fluoro-2-(vinyloxy)-benzaldehyde.
4. The method for preparing the fiberglass reinforced plastic thread elastic sealant according to claim 3, characterized in that: In S1, the mass ratio of 5-bromo-3-fluoro-2-hydroxybenzaldehyde to dibromoethane is (18-23):(20-26).
5. The method for preparing the fiberglass reinforced plastic thread elastic sealant according to claim 3, characterized in that: In S1, the mass ratio of dibromoethane to anhydrous potassium carbonate is (20-26): (13-20).
6. The method for preparing the fiberglass reinforced plastic thread elastic sealant according to claim 3, characterized in that: In S1, the first set temperature is 75 to 85° C., and the first set time is 15 to 17 hours.
7. The method for preparing the fiberglass reinforced plastic thread elastic sealant according to claim 3, characterized in that: In S2, the mass ratio of 5-bromo-3-fluoro-2-(2-bromoethoxy)-benzaldehyde to potassium tert-butoxide is (17-23):(5-10).
8. The method for preparing the fiberglass reinforced plastic thread elastic sealant according to claim 3, characterized in that: In S2, the second set temperature is -18 to -22°C, the third set temperature is -17 to -22°C, and the second set time is 1 to 2 hours.
9. Use of the fiberglass reinforced plastic thread elastic sealant according to claim 1 in fiberglass reinforced plastic pipes.
Citation Information
Patent Citations
Fiber glass reinforced plastic pipe thread sealing grease and preparation method thereof
CN101586020A
Dynamic sealant and preparation method thereof
CN102250470A
Bi-component polysulfide sealant and preparation method thereof
CN102618207A
Two-component modified polysulfide sealant capable of being vulcanized under low temperature
CN107936907A
High-flash-point pipeline anticorrosion polysulfide modified polyurea coating and preparation method thereof
CN114058254A
